The β1 subunit of the Na,K-ATPase pump interacts with megalencephalic leucoencephalopathy with subcortical cysts protein 1 (MLC1) in brain astrocytes: new insights into MLC pathogenesis - Brignone, Maria S. (Oxford University Press, 2011)
Megalencephalic leucoencephalopathy with subcortical cysts (MLC) is a rare congenital leucodystrophy caused by mutations in MLC1, a membrane protein of unknown function. MLC1 expression in astrocyte end-feet contacting blood vessels and meninges, along with brain swelling, fluid cysts and myelin vacuolation observed in MLC patients, suggests a possible role for MLC1 in the regulation of fluid and ion homeostasis and cellular volume changes. To identify MLC1 direct interactors and dissect the molecular pathways in which MLC1 is involved, we used NH(2)-MLC1 domain as a bait to screen a human brain library in a yeast two-hybrid assay. We identified the β1 subunit of the Na,K-ATPase pump as one of the interacting clones and confirmed it by pull-downs, co-fractionation assays and immunofluorescence stainings in human and rat astrocytes in vitro and in brain tissue. By performing ouabain-affinity chromatography on astrocyte and brain extracts, we isolated MLC1 and the whole Na,K-ATPase enzyme in a multiprotein complex that included Kir4.1, syntrophin and dystrobrevin. Because Na,K-ATPase is involved in intracellular osmotic control and volume regulation, we investigated the effect of hypo-osmotic stress on MLC1/Na,K-ATPase relationship in astrocytes. We found that hypo-osmotic conditions increased MLC1 membrane expression and favoured MLC1/Na,K-ATPase-β1 association. Moreover, hypo-osmosis induced astrocyte swelling and the reversible formation of endosome-derived vacuoles, where the two proteins co-localized. These data suggest that through its interaction with Na,K-ATPase, MLC1 is involved in the control of intracellular osmotic conditions and volume regulation in astrocytes, opening new perspectives for understanding the pathological mechanisms of MLC disease.